The role of business accelerators and incubators in supporting entrepreneurial projects in the entertainment sector and their impact on domestic tourism in the Kingdom in light of the Covid-19 pandemic - Al-Shanbari, Jehan Abdullah; Bukhari, Dareen Muhammad; Al-Buqami, Sanaa Fahm; Qari Bey, Dania Habibullah (Journal of Economic, Administrative and Legal Sciences, 2023)
As a result of the challenges faced by the Kingdom in the light of the Covid-19 pandemic of economic stagnation and negative economic and social effects, the Kingdom determined its efforts to overcome the crisis, and succeeded with the great interest it gave to the entertainment sector, helped to its renaissance and development and reflected positively on domestic tourism in the Kingdom, through the establishment of incubators and accelerators entertainment business that had the greatest impact in supporting start-up entrepreneurship and entrepreneurs, the entertainment sector and domestic tourism in the Kingdom became suppliers Important economists, made the Kingdom among the countries of the world and became an important economic interface to attract tourists from home and abroad, the current study adopted the analytical descriptive approach and used the questionnaire as a tool for collecting data, representing the study community of all entrepreneurs entrepreneurs emerging and embraced in accelerators and incubators entertainment business in addition to investors in the entertainment and domestic tourism sectors in the Kingdom, while the sample of the study was 12 leading companies incubated, The results of the study indicated the impact of speeding and incubators on the success of entrepreneurial projects, and the existence of a relationship between the development of entertainment and the development of domestic tourism in the Kingdom, and the most prominent recommendations were to increase the number of accelerators and incubators in the entertainment sector in the Kingdom.